Hu, Ter HUBUNGAN NILAI TUKAR RUPIAH TERHADAP INDEKS HARGA SAHAM GABUNGAN (IHSG) - Agustina, Putri Padila; Adji, Bimo; Enjelika, Meliza; Rahmah, Yuni Afifah; Tarigan, Dinta; Nasution, Nurhayati (Management Insight: Jurnal Ilmiah Manajemen, 2026)
This study aims to analyze the relationship between the Rupiah exchange rate and the Composite Stock Price Index (IHSG) in Indonesia. The research employs a quantitative approach using secondary data in the form of monthly Rupiah exchange rate against the US dollar and IHSG data from January 2020 to December 2025. The analysis techniques include classical assumption tests, Pearson correlation, and simple linear regression. The results show that the exchange rate has a positive and significant relationship with IHSG, with a correlation coefficient of 0.534 and a significance level below 0.001. The regression model also indicates that the exchange rate significantly affects IHSG with a contribution of 28.5%. These findings suggest that exchange rate movements are an important factor influencing the dynamics of the capital market in Indonesia.